Pesticide-Residue Relationship And Its Adverse Effects On Occupational Workers In Dakahlyia, Egypt (Applied Biological Research, 2012)
This study was designed to determine pesticide residues in blood, evaluate its effect on biochemical parameters and assess adverse health  effects in farmers, pesticide market-workers and pesticide spray workers. The level of awareness or knowledge about precautionary measures for pesticides safety was also assessed. The field survey  indicated that 40.0, 6.7 and 12.0% of farmers, market-workers and  spray-workers, respectively, did not wear protective clothing. However, most of them (83.3, 93.3 and 88.0%) had knowledge about the safety  precautions to be taken during pesticide formulation and application.  Significant decrease in hemoglobin level and platelet count was detected  in spray-workers, but significant increase in white blood cell count was  noticed in pesticide-market workers and spray-workers. No significant  changes were observed in liver function, but significant inhibition in  acetylcholine esterase activity and significant increase in prothrombin  time were noticed in all pesticide-exposed subjects. A significant rise in  urea concentration was observed in pesticide-spray workers, but no  significant differences in creatinine level were seen. The residue analysis  revealed that 76.7, 92.5 and 100.0% of farmers and market- and spray workers, respectively, had insecticide residues in their blood. Also, most  of the study subjects had multiple residues above the acceptable daily  intake. Therefore, creating the awareness among pesticide users to  improve and encourage safe use and handling of pesticides through education, proper guidance and fore-warning about the risks involved in  misuse of poisonous materials are required.
Keywords: Biochemical markers; Egypt; occupational workers; pesticide exposure; pesticide residues; precautions; safety